Accumulation of some heavy metals in the prevailing plants (Alhagi mourorum and Suaeda vermiculata) near the thermal power plant in Al-Nasiriyah city south of Iraq - N. Faris , Huda; R. Malah , Hyder; Y. Al-khafagii, Bassim (University of Thi-Qar Journal of Science, 2018)
The present study aims to investigate the effect of Thermal power plant emissions upon two species of plant Alhagi mourorum and Suaeda vermiculata which growth in the region close to Thermal power plant. triplicater samples were collected seasonllys from autumn 2016 up to summer 2017 one time from each season. three station were selected in the study area to execute this study meters. The first station distances 400 meters from the thermal power station, The second station is located 800 meters from the thermal power plant . While, the third station distances 1200 meters from the thermal power plant . Three stations were with prevailing wind direction (north wind) , while control station situated far from the thermal power plant about 12 km. the concentratios of heavy metals Cd, Cu, Pb and Zn were estimate in root and shoot systems for both plants, their concentration in root system more higher than their concentrations in shoot system. its concluded from the present study that thermal electric power station emissions affected upon the plants which growth in the surrounding region with thermal power plant.